Nucleotide Composition of Nucleic Acids of Fungi I. Ribonucleic Acids - Storck, Roger (1965)
Storck, Roger (The University of Texas, Austin). Nucleotide composition of nucleic acids from fungi. I. Ribonucleic acids. J. Bacteriol. 90:1260–1264. 1965.—The nucleotide composition of the ribonucleic acids (RNA) present in extracts of 26 species of fungi was determined. The results were analyzed, together with those in the literature. It was found that the content in moles per cent of guanine plus cytosine (GC content) varied from 44.1 to 60.5 in a distribution composed of 8 species of zygomycetes, 10 of ascomycetes, 11 of deuteromycetes, and 8 of basidiomycetes. The GC-content range and average were, respectively, 44.1 to 49.3 and 46.4 for the zygomycetes, 47.4 to 54.4 and 50.2 for the ascomycetes, 48.2 to 54.5 and 51.6 for the deuteromycetes, and 50.4 to 60.5 and 52.4 for the basidiomycetes. The GC content averaged 45.6 and ranged from 44.1 to 46.3 for four Mucor species. In addition, GC contents significantly lower than 50 were also encountered in some species of Hemiascomycetidae, suggesting that AT type RNA is not uncommon in fungi. It was proposed that the base composition of fungal RNA might have a taxonomic and phylogenetic significance.